Is it possible to achieve a safe glycated hemoglobin level during intensive hypoglycemic therapy? (results of ADVANCE study) - Marina Vladimirovna Shestakova; Minara Shamkhalovna Shamkhalova (Сахарный диабет)
Aim. To study efficacy of glycemic control in terms of reduced HbA1c level using glyclazide modified release (MR) in patients with DM2 and differentclinical characteristics at the initial stage of therapy in the framework of ADVANCE study (Action in Diabetes and Vascular Disease: Preterax andDiamicron Modified Release (MR) Controlled Evaluation). Materials and methods. A total of 11140 patients aged 55 years or older with DM2 and one or several cardiovascular risk factors were randomized forthe study. They were randomly distributed between 2 groups, one to receive intensive hypoglycemic therapy with glyclazide MR the other to be treatedin a standard mode as recommended by local, regional or national guidelines after a 6 week introductory phase. The efficacy of therapy was assessedbased on the following criteria: absolute change in HbA1c level (difference between the last and the first values obtained during the randomizationperiod), real HbA1c level achieved, percent of patients with target HbA1c level (